LO087: Emergency department patients' connection to primary care providers: reasons for lack of connection. (2nd June 2016) - Krebs, L.; Kirkland, S.W.; Crick, K.; Villa-Roel, C.; Davidson, A.; Voaklander, B.; Holroyd, B.; Cross, E.; Nikel, T.; Chetram, R.; Couperthwaite, S.; Cummings, G.; et al.
Abstract : Introduction: Some non-urgent/low-acuity Emergency Department (ED) presentations are considered convenience visits and potentially avoidable with improved access to primary care services. This study surveyed patients who presented to the ED and explored their self-reported reasons and barriers for not being connected to a primary care provider (PCP).Methods: Patients aged 17 years and older were randomly selected from electronic registration records at three urban EDs in Edmonton, Alberta (AB), Canada. Following initial triage, stabilization, and verbal informed consent, patients completed a 47-item questionnaire. Data from the survey were cross-referenced to a minimal patient dataset consisting of ED and demographic information. The questionnaire collected information on patient characteristics, their connection to a PCP, and patients' reasons for not having a PCP.Results: Of the 2144 eligible patients, 1408 (65.7%) surveys were returned and 1402 (65.4%) were completed. The majority of patients (74.4%) presenting to the ED reported having a family physician; however, the 'closeness' of the connection to their family physician varied greatly among ED patients with the most recent family physician visit ranging from 1 hour before ED presentation to 45 years prior. Approximately 25% of low acuity ED patients reported no connection with a family physician. Reasons for a lack of PCP connection included: prior physician retired, left, or died (19.8%), they had never tried to find one (19.2%), they had recently moved to Alberta (18.0%), and they were unable to find one (16.5%).Conclusion: A surprisingly high proportion of ED patients (25.6%) have no identified PCP. Patients had a variety of reasons for not having a family physician. These need to be understood and addressed in order for primary care access to successfully contribute to diverting non-urgent, low acuity presentations from the ED.